Paikem Model Pembelajaran Alternatif Bagi Anak Usia Dini - Naila Fikrina Afrih Lia; Setyo Sekar sari (FITK UIN Walisongo Semarang, 2021)
The Active, Innovative, Creative, Effective and Fun Learning Model (PAIKEM) is one of the various child centered learning models. The PAIKEM model is appropriate to be implemented in PIAUD institutions because it is in accordance with the characteristics of early childhood. PIAUD educator needs to fully understand the essence of PAIKEM to create a quality learning. This research uses literature study method with the formulation of the problem how the PAIKEM model design and implementation in the PIAUD institution. The results showed that the PAIKEM model is appropriate to be implemented in PIAUD institutions because the characteristics of the PAIKEM model are in accordance with the psychological development of early childhood where children play while learning. Educators can also optimize the potential of the surrounding environment as a creative and innovative learning resource, as well as create childfriendly, learning media by providing effective and fun games so that children become more active, innovate, and be creative to add to their experiences.